(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
The text discusses the trade of ceramic products in the Aosta Valley, specifically within the context of the Castle of Quart. Despite the challenges posed by the mountainous terrain, the region was an important commercial crossroads due to its location along the trade route connecting the passes of the Little and Great St. Bernard. This steady flow of goods included ceramics from various production centers, as evidenced by archaeological finds at the Castle of Quart. Excavations have uncovered ceramic materials from different periods, dating back both to the time when the castle was inhabited by the Lords of Quart in the 14th century and to the 15th-16th centuries when it was administered by castellans appointed by the Counts of Savoy. The study focuses on analyzing these ceramics, highlighting their diverse origins, ranging from the Piedmont region to Middle Eastern artifacts. The ceramics reflect the cultural exchange and variety of commercial trade routes that passed through this alpine region, emphasizing its historical role as a key hub for goods and cultural influences.